Analisis Kejenuhan Mahasiswa dalam Mengikuti Perkuliahan Daring - Fitriyana Fitriyana; Sedya Sentosa (ISLAMIKA, 2022)
This study aims to analyze and understand the factor of student boredom in attending online lectures during the Covid-19 pandemic and how appropriate learning strategies are in online lectures. The research method uses a qualitative approach to phenomenology. Sources of data were obtained from two sources, namely primary data sources generated from interviews with students and lecturers and secondary data as reinforcement of the results of interviews and observations that had been carried out. Data collection system is done through interviews, observation and documentation. The data analysis technique uses the Miles and Huberman analysis model which consists of three processes, namely data reduction, data presentation, and drawing conclusions. The results of the study indicate that various problems arise in the implementation of online lectures, ranging from the readiness of lecturers and students, the technological infrastructure they have and the internet network. Therefore, in overcoming the various problems that exist, researchers have found strategies that can be applied to minimize the level of student boredom in attending online lectures, namely by developing online learning methods that are more flexible and can expand the use of learning media by utilizing networks. social.